Epidermolysis bullosa simplex generalized severe induces a T helper 17 response and is improved by apremilast treatment. (2nd December 2018) - Castela, E.; Tulic, M.K.; Rozières, A.; Bourrat, E.; Nicolas, J.‐F.; Kanitakis, J.; Vabres, P.; Bessis, D.; Mazereeuw, J.; Morice‐Picard, F.; Baty, D.; Berard, F.; et al.
Summary: Background: Epidermolysis bullosa simplex generalized severe (EBS‐gen sev) is a genetic disorder caused by mutation in the KRT5 or KRT14 genes. Although it is usually considered a mechanical disease, recent data argue for additional inflammatory mechanisms. Objectives: To assess the inflammation in the skin of patients with EBS‐gen sev. Methods: A first immunohistochemical retrospective study was performed on frozen skin samples from 17 patients with EBS‐gen sev. A second multicentre prospective study was conducted on 10 patients with severe EBS‐gen sev. Blister fluid and epidermis were processed for immunochemical analysis and quantitative real‐time polymerase chain reaction. Cytokine expression was analysed in blister fluid and compared with that in controls. Results: Histological analysis showed a constant dermal perivascular CD4 + lymphocyte infiltrate in skin biopsies of both blister ( n = 17) and rubbed skin ( n = 5), an epidermal infiltration of neutrophils and eosinophils in 70% of cases, and increased immunostaining for CXCL9 and CXCL10 in blistering skin. High levels of T helper 17 cytokines were detected in lesional skin. Three adult patients with EBS‐gen sev were treated with apremilast, with a dramatic improvement of skin blistering and good tolerance. Conclusions: Our study demonstrates the importance of inflammation in patients with EBS‐gen sev and underlines the key role for T helper 17 cells in its pathogenesis. In addition, this study provides promising new therapeutic approaches for this disabling disorder. Abstract : What's already known about this topic? Epidermolysis bullosa simplex generalized severe (EBS‐gen sev) is a rare disabling skin disorder related to skin fragility. What does this study add? We showed the presence of an immune infiltrate characterized by a T helper (Th)17 phenotype in the skin of patients with EBS‐gen sev. There was a marked improvement of the skin condition in patients with EBS after treatment with apremilast, an anti‐Th17 molecule. What is the translational message? Our results demonstrate the importance of inflammation in EBS‐gen sev and underline the key role of Th17 activation. Anti‐Th17 molecules such as apremilast provide a promising new therapeutic approach for this disabling disorder. Linked Comment:  Mellerio. Br J Dermatol 2019;180 :258–260 . Plain language summary available online Respond to this article